The use of the Eurosystem's monetary policy instruments and its monetary policy implementation framework Q2 2016 - Q4 2017 - Alexander Bock; Miha Cajnko; Svetla Daskalova; Iwona Durka; Brian Gallagher; Roel Grandia; Glenn Haberbush; Annette Kamps; Alaoíshe Luskin; Michelina Lo Russo; Ma Carmen Castillo Lozoya; Filippo Pasqualone; et al. (European Central Bank (ECB), 2018)
This paper provides a comprehensive overview of the use of the Eurosystem's monetary policy instruments and the operational framework from the second quarter of 2016 to the last quarter of 2017. It reviews the context of Eurosystem market operations; the design and operation of the Eurosystem's counterparty and collateral frameworks; the fulfilment of minimum reserve requirements; participation in credit operations and recourse to standing facilities; and the conduct of outright asset purchase programmes. The paper also discusses the impact of monetary policy implementation on the Eurosystem's balance sheet, excess liquidity and money market liquidity conditions.
Keywords: D02; E43; E58; E65; G01; 330; monetary policy implementation; central bank counterparty framework; central bank collateral framework; central bank liquidity management; non-standard monetary policy measures